Tools for interpreting Christ's saving mysteries in scripture: Aquinas on reduplicative propositions in christology - Moser, David J. ca. 20./21. Jh. (Scottish journal of theology, 2020)
This article examines how Thomas Aquinas used reduplicative propositions (e.g. "Christ suffers insofar as he is a human being") to explicate Christ's saving mysteries, or events that Christ did and suffered that produced states of affairs only God can do. Following scripture's focus on Christ as one acting subject, Aquinas argued that we should use the adverbial modifiers "authoritatively as God and instrumentally as a human being" to speak well of Christ's saving mysteries as actions of a single subject. This approach is theologically beneficial because it avoids the pitfalls of thinking of Christ's natures as agents.